DEPENDENT PARAMETERS DEGRADATION RELIABILITY ASSESSMENT BASED ON JEFFREYS NONINFORMATIVE PRIOR PARAMETERS - YIN ZeKai; GUO Yu (Jixie qiangdu)
The correlation between the parameters of the Gamma degradation process was described by the Jeffreys uninformative prior distribution. And the Bayesian model was used to obtain the full conditional distribution of each parameter. The MCMC method was used to get parameter posterior expectation estimates. Finally, reliability was calculated according to the engineering examples and 100 simulations, the obtained reliability assessment was more conservative than the independent case in engineering practice. Thus, the product repair suggestion could be given earlier. And the higher the reliability requirement was .the oreater the deviation between the estimation results of the correlated case and the independent case was, and the life estimation error rate under the reliability of 0. 999 9 was up to 9.26%.